(untitled) (Historia, 2021)
Most of South African history which is documented coincides with the arrival of Europeans, specifically the Dutch and their first contact with the Khoi‐Khoi. The history of the British in South Africa, however, coincides largely with that of the Zulus, especially from the period when Shaka was the Zulu king. In this publication, John Laband provides a succinct narrative of the history of the Zulu from the period of Shaka until the reign of Goodwill Zwelithini. In this period, there were no fewer than eight Zulu kings: Shaka, Dingane, Mpande, Cetshwayo, Dinuzulu, Solomon, Cyprian and Goodwill Zwelithini. Laband highlights the changes in the social structure, customs, and political circumstances during the reign of each of these monarchs, and elaborates on how they used their powers to achieve certain social and political objectives within the Zulu kingdom.